Method for preparing in-situ carbon-coated transition metal sulfide and application of in-situ carbon-coated transition metal sulfide
The preparation of in-situ carbon-covered transition metal sulfides through microwave solvothermal reactions solves the problems of poor conductivity and volume expansion of transition metal sulfides in sodium ion batteries, and achieves efficient sodium ion battery performance improvement and green synthesis process, which is suitable for sodium ion battery negative electrode materials.
Patent Information
- Application Number
- CN202510515622.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-23
- Publication Date
- 2025-07-18
AI Technical Summary
Transition metal sulfides have problems such as poor conductivity, volume expansion and structural powdering, polysulfide shuttle effect, interface side reactions and SEI film instability, insufficient mechanical stability and difficult synthesis and processing in battery energy storage materials, which limit their application in sodium ion batteries.
The metal organic frame material is mixed with a sulfur source through microwave solvothermal reaction to prepare in situ carbon-coated transition metal sulfides. The carbon frame and microwave solvothermal reaction of MOF materials are used to optimize the synthesis process, shorten the time and improve the material's conductivity and structural stability.
It improves the fast charging performance and low-temperature usage characteristics of sodium ion batteries, enhances the conductivity and structural stability of the material, alleviates volume expansion, reduces side reactions, improves the overall performance and cycle stability of the battery, and provides a green and environmentally friendly industrial production path.
Smart Images

Figure CN120341266A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energy storage, and particularly relates to a method for preparing in-situ carbon-coated transition metal sulfide and its application. Background Art
[0002] Sodium-ion batteries have successfully achieved the leap from laboratory to industrial demonstration with their significant resource endowment advantages (sodium resource abundance is 420 times that of lithium), excellent intrinsic safety (thermal runaway temperature is higher than that of lithium batteries), and wide temperature range adaptability (-40 to 80 °C), showing unique competitiveness in the fields of low-speed transportation and grid-scale energy storage. With technological breakthroughs in all links of the industrial chain, its industrialization process is accelerating. However, in the face of the increasing demand for high energy density (currently 120-160 Wh / kg vs. 200-300 Wh / kg for lithium batteries), developing a new system with both high specific energy (>200 Wh / kg) and long cycle life (>5000 times) has become a key issue. In the field of anode materials, although hard carbon materials have achieved commercial application, their inherent sodium precipitation phenomenon (which easily causes electrolyte decomposition) and low specific capacity (~300 mAh / g) limit performance improvement. In contrast, transition metal sulfides (such as MoS2, FeS2) have become the research focus of a new generation of high-safety and high-specific-energy sodium battery anodes due to their breakthrough theoretical capacity (500-1000 mAh / g), fast sodium ion diffusion kinetics (fast charging performance improved by more than 30%), and intrinsic high redox potential (effectively inhibiting sodium dendrite formation).
[0003] Although transition metal sulfides have advantages such as high theoretical capacity and low redox potential when used as battery energy storage materials (such as anodes of lithium / sodium-ion batteries), the following main defects still exist in their practical applications:
[0004] 1. Poor conductivity
[0005] Transition metal sulfides generally have the problem of low intrinsic conductivity, resulting in low electron transport efficiency of electrode materials, which in turn affects the rate performance and cycle stability of the battery. For example, the conductivity of molybdenum disulfide (MoS2) is significantly lower than that of graphene or carbon-based composites, and it needs to be improved by nanosizing or compounding with high-conductivity materials (such as graphene, carbon nanotubes).
[0006] 2. Volume expansion and structural pulverization
[0007] During the charge and discharge process, transition metal sulfides will cause serious volume expansion (usually exceeding 200%) through conversion reactions (such as lithiation / sodiation reactions of sulfides). For example, the volume expansion of SnS2 can reach 300% during sodium ion insertion. Repeated expansion and contraction will cause material particle pulverization and electrode structure collapse, resulting in rapid capacity decay and shortened cycle life.
[0008] 3. Polysulfide shuttle effect
[0009] In lithium-sulfur batteries, sulfide materials are prone to react with the electrolyte to form soluble polysulfides (such as Li2S x ), and these substances will diffuse from the positive electrode to the negative electrode and react with lithium metal, resulting in the loss of active materials, the reduction of Coulomb efficiency, and the attenuation of battery capacity. This problem also exists in sodium-sulfur batteries.
[0010] 4. Interface side reactions and instability of the SEI film
[0011] Transition metal sulfides will have side reactions with the electrolyte during the first charge and discharge process, generating an unstable solid electrolyte interface (SEI) film. For example, iron disulfide (FeS2) in sodium-ion batteries causes an increase in internal resistance and capacity loss due to the repeated rupture and regeneration of the SEI film.
[0012] 5. Insufficient mechanical stability and cycling performance
[0013] Some sulfide materials (such as cobalt sulfide and nickel sulfide) are prone to crack and delaminate during cycling due to the difficulty of releasing structural stress, resulting in the contact failure between the electrode and the current collector. For example, the capacity retention rate of pure MoS2 in sodium-ion batteries is less than 50% after 100 cycles.
[0014] 6. Difficulties in synthesis and processing
[0015] The synthesis and processing conditions of transition metal sulfides are relatively harsh, and it is difficult to achieve large-scale industrial production. For example, the preparation of sulfide electrolytes requires strict control of the moisture and oxygen content, otherwise it will lead to a decline in material performance.
[0016] In summary, transition metal sulfides have high theoretical capacity and electrochemical activity in battery energy storage materials, but they still face many challenges in practical applications and need further research and optimization to overcome these defects. Summary of the Invention
[0017] To solve the above technical problems, the present invention proposes a method for preparing in-situ carbon-coated transition metal sulfides and its application. The present invention obtains in-situ carbon-coated transition metal sulfide materials through microwave solvothermal reaction, effectively improving the fast charging performance of the battery and endowing the battery with low-temperature use characteristics.
[0018] To achieve the above object, the present invention provides the following technical solutions:
[0019] One of the technical solutions of the present invention:
[0020] The present invention provides a method for preparing in-situ carbon-coated transition metal sulfide, comprising the following steps: adding a metal-organic framework material (MOF material) and a sulfur source into a mixed solvent, and obtaining the in-situ carbon-coated transition metal sulfide through a microwave solvothermal reaction.
[0021] Preferably, the mass of the sulfur source is 0.25 - 10 times that of the MOF material. Exemplarily, the mass ratio of the MOF material to the sulfur source is 1:4, 1:10, 4:1, 2:5, 1:6, 1:1, 1:5, 1:3, 3:2, 3:8 or 2:1.
[0022] Exemplarily, the sulfur source includes one of thiourea, sodium thiosulfate and thioacetamide.
[0023] Furthermore, the mixed solvent is a mixed solvent of deionized water and absolute ethanol.
[0024] Preferably, the volume ratio of the deionized water to the absolute ethanol is (1 - 3):1. Exemplarily, the volume ratio of the deionized water to the absolute ethanol is 3:1, 1:1 or 2:1.
[0025] Furthermore, the microwave solvothermal reaction is carried out under stirring conditions.
[0026] Furthermore, the parameters of the microwave solvothermal reaction are: the reaction temperature is 80 - 200 °C, the reaction time is 30 - 120 min, the heating rate is 5 - 10 °C / min, the microwave power is 300 - 800 W, and the stirring speed is 800 - 2000 rpm.
[0027] In the present invention, the transition metal sulfide is synthesized using the MOF material as a precursor, retaining the carbon framework of the precursor MOF, saving the step of additional carbon coating. Moreover, the present invention synthesizes the in-situ carbon-coated transition metal sulfide by microwave solvothermal method, greatly shortening the synthesis time and optimizing the preparation process of the in-situ carbon-coated transition metal sulfide.
[0028] The present invention does not limit the source of the MOF material, which can be directly obtained by purchase or synthesized according to the existing technology.
[0029] When the MOF material is synthesized according to the existing technology, the preparation steps of the MOF material are as follows: dissolving a metal coordination ion compound and an organic compound in a mixed solvent of deionized water and absolute ethanol, and obtaining the MOF material through a microwave solvothermal reaction.
[0030] In the preparation method of the MOF material, the volume ratio of the deionized water to the absolute ethanol is (1 - 3):1. Exemplarily, the volume ratio of the deionized water to the absolute ethanol is 3:1, 1:1 or 2:1.
[0031] In the preparation method of the MOF material, the metal coordination ion compound includes one of Fe(NO3)3·9H2O, Cu(NO3)2·3H2O, Co(NO3)2·6H2O, (NH4)6Mo7O 24 ·4H2O and Ni(NO3)2·6H2O.
[0032] In the preparation method of the MOF material, the organic compound includes one of trimesic acid (1,3,5-benzenetricarboxylic acid), trimellitic acid (1,2,4-benzenetricarboxylic acid), pyromellitic acid (1,2,3-benzenetricarboxylic acid) and pyromellitic acid hydrate.
[0033] In the preparation method of the MOF material, the mass ratio of the metal coordination ion compound to the organic compound is (1-5):(1-10). Exemplarily, the mass ratio of the metal coordination ion compound to the organic compound is 2:1, 1:1, 4:1, 1:6, 1:10, 1:5, 3:1, 5:1, 5:7, 1:4, 1:2 or 2:5.
[0034] In the preparation method of the MOF material, the parameters of the microwave solvothermal reaction are: the reaction temperature is 80-200 °C, the reaction time is 30-120 min, the heating rate is 5-10 °C / min, the microwave power is 300-800 W, and the stirring speed is 800-2000 rpm.
[0035] Compared with directly purchasing the MOF material, the cost of preparing the MOF material using the metal coordination ion compound and the organic compound is lower.
[0036] The second technical solution of the present invention:
[0037] The present invention also provides an in-situ carbon-coated transition metal sulfide obtained by the above method.
[0038] The third technical solution of the present invention:
[0039] The present invention also provides the application of the above in-situ carbon-coated transition metal sulfide in the preparation of battery energy storage materials.
[0040] Further, the battery energy storage material is a battery energy storage negative electrode material.
[0041] Even further, the battery energy storage negative electrode material is a sodium-ion battery negative electrode material.
[0042] Compared with the prior art, the present invention has the following advantages and technical effects:
[0043] Aiming at the disadvantages of existing hard carbon materials for the negative electrode of sodium-ion batteries, such as unsafe sodium deposition at low potential and low capacity, the present invention rapidly synthesizes an in-situ carbon-coated transition metal sulfide material (in-situ carbon-coated transition metal sulfide) by microwave solvothermal reaction of MOF materials with different sulfur sources, and applies it to the field of energy storage battery materials (for example, as the negative electrode material of sodium-ion batteries). This not only enables the rapid preparation of in-situ carbon-coated transition metal sulfide, but also enhances the electrical conductivity and structural stability of the material itself. In-situ carbon coating can improve the electronic conductivity of the material, relieve the stress caused by volume expansion, protect the material from side reactions with the electrolyte, and improve the overall performance of the battery. The battery prepared using the in-situ carbon-coated transition metal sulfide of the present invention has excellent performance in terms of low temperature, high capacity, and fast charging.
[0044] Compared with the traditional hydrothermal method, the present invention synthesizes in-situ carbon-coated transition metal sulfide by microwave solvothermal reaction. The heating method is from the inside out, which greatly shortens the synthesis time. In addition, the present invention can monitor the reaction pressure inside the tank, does not require complex preparation conditions, materials, and equipment, and the preparation method is simple; it does not produce polluting and toxic gases, is green and environmentally friendly, and is safe and controllable. This synthesis strategy with the characteristics of high efficiency, precision, and environmental protection provides a breakthrough industrial production path for the large-scale application of transition metal sulfides in energy storage systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] The drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The schematic embodiments and descriptions thereof are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0046] Figure 1 It is a morphology diagram of the in-situ carbon-coated transition metal sulfide material in Example 1.
[0047] Figure 2 It is the cycle performance curve and Coulomb efficiency curve of the battery assembled with the product of Example 1 at a current density of 1 A·g -1 when.
[0048] Figure 3 It is the cycle performance curve and Coulomb efficiency curve of the battery assembled with the product of Example 1 at a current density of 5 A·g -1 when.
[0049] Figure 4 It is the cycle performance curve and Coulomb efficiency curve of the battery assembled with the product of Example 1 at a low temperature of -20 °C and a current density of 0.1 A·g -1 when.
[0050] Figure 5 It is the cycle performance curve of the battery assembled with the commercial copper sulfide for comparison in Example 1 at a current density of 1 A·g-1 Cycling performance curve and Coulomb efficiency curve at
[0051] Figure 6 Morphology diagram of copper sulfide obtained in Comparative Example 1.
[0052] Figure 7 For the battery assembled with the transition metal sulfide material in Comparative Example 1 at a current density of 1 A·g -1 Cycling performance curve and Coulomb efficiency curve at Detailed implementation manners
[0053] Now, various exemplary implementation manners of the present invention will be described in detail. This detailed description should not be considered as a limitation to the present invention, but should be understood as a more detailed description of certain aspects, characteristics, and implementation schemes of the present invention.
[0054] It should be understood that the terms described in the present invention are only used to describe specific implementation manners and are not used to limit the present invention. Additionally, for the numerical ranges in the present invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each intermediate value within any stated value or stated range, as well as each smaller range between any other stated value or intermediate value within the stated range, is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded from the range.
[0055] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention pertains. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein can also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In case of conflict with any incorporated document, the content of this specification shall prevail.
[0056] Without departing from the scope or spirit of the present invention, various improvements and changes can be made to the specific implementation manners of the present invention specification, which are obvious to those skilled in the art. Other implementation manners obtained from the present invention specification are obvious to those skilled in the art. The present invention specification and examples are only exemplary.
[0057] Regarding the use of "comprising", "including", "having", "containing", etc. in this article, they are all open-ended terms, meaning including but not limited to.
[0058] An embodiment of the present invention provides a method for preparing in-situ carbon-coated transition metal sulfide, including the following steps: adding a metal-organic framework material (MOF material) and a sulfur source into a mixed solvent, and obtaining in-situ carbon-coated transition metal sulfide through a microwave solvothermal reaction.
[0059] In-situ carbon coating can synchronously achieve the growth of carbon layers during the formation of transition metal sulfides, making the combination between the carbon layer and the sulfide tighter and more uniform. This endogenous coating method avoids the problem of poor interfacial combination in traditional exogenous carbon coating, thus significantly improving the stability and electrochemical performance of the material. The carbon coating layer can effectively improve the conductivity of the material and reduce electrode polarization, which is crucial for improving the charge-discharge rate and cycle stability of lithium-ion batteries. In-situ carbon coating can also prevent the aggregation of transition metal sulfide particles during preparation and use, and at the same time alleviate volume expansion during charge and discharge, reducing the structural damage of the material.
[0060] Compared with the traditional step-by-step coating method, the in-situ carbon coating of the present invention can complete the synthesis of transition metal sulfides and the formation of carbon layers in one-step reaction. This method simplifies the process flow and reduces the production cost.
[0061] In the embodiments of the present invention, the mass of the sulfur source is 0.25 - 10 times the mass of the MOF material. Exemplarily, the mass ratio of the MOF material to the sulfur source is 1:4, 1:10, 4:1, 2:5, 1:6, 1:1, 1:5, 1:3, 3:2, 3:8 or 2:1. When the mass ratio of the sulfur source to the MOF material is appropriate, the initial morphology of the MOF can be better retained. However, if the mass ratio is inappropriate, it may lead to a significant change in morphology. The mass ratio of the sulfur source to the MOF material also directly affects the electrochemical performance of the material. The materials prepared within the scope of the present invention exhibit excellent specific capacitance and cycle stability. In addition, the selection of the sulfur source and the mass ratio also affect the conductivity and ion diffusion ability of the material. An appropriate mass ratio can optimize the thickness and uniformity of the carbon coating layer, thereby affecting the stability and other properties of the material.
[0062] In the embodiments of the present invention, the sulfur source is selected from one of thiourea, sodium thiosulfate and thioacetamide. These materials can promote the formation of nano-scale particles or nano-dot structures of transition metal sulfides during the reaction. The nano-structure has a larger specific surface area and a shorter ion diffusion path, which helps to improve the electrochemical activity and rate performance of the material. Raw materials such as thiourea, sodium thiosulfate and thioacetamide are relatively environmentally friendly, avoiding the use of toxic and harmful organic sulfides or hydrogen sulfide gas, meeting the requirements of green chemistry.
[0063] In the embodiments of the present invention, the mixed solvent is a mixed solvent of deionized water and absolute ethanol, and preferably the volume ratio of deionized water to absolute ethanol is (1 - 3):1. Exemplarily, the volume ratio of deionized water to absolute ethanol is 3:1, 1:1 or 2:1.
[0064] In an embodiment of the present invention, the microwave solvothermal reaction is carried out under stirring conditions. Preferably, the parameters of the microwave solvothermal reaction are: the reaction temperature is 80 - 200 °C, the reaction time is 30 - 120 min, the heating rate is 5 - 10 °C / min, the microwave power is 300 - 800 W, and the stirring speed is 800 - 2000 rpm.
[0065] The reaction temperature is one of the key factors affecting the morphology and properties of the material. In the microwave solvothermal reaction, as the reaction temperature increases, the activity of the reactants enhances, which is beneficial to the growth of crystals and the formation of structures. However, too high a temperature may lead to excessive pressure in the reaction system, causing danger, and may also lead to the decomposition or phase change of the material, thus affecting its properties. Therefore, it is necessary to select an appropriate reaction temperature to ensure good morphology and properties of the material. Specifically, the sulfur source will undergo a hydrolysis reaction at high temperatures, generating sulfide ions and combining with metal ions to form sulfides. Too high a temperature may accelerate this reaction process, resulting in the rapid growth and aggregation of sulfide crystals, thus affecting the dispersibility and uniformity of the material. On the contrary, too low a temperature may make the reaction proceed slowly, which is not conducive to the formation of crystals and the improvement of structures.
[0066] The reaction time is also an important factor affecting the morphology and properties of the material. In the microwave solvothermal reaction, the extension of the reaction time is usually beneficial to the improvement of crystal structures and properties. However, too long a reaction time may also lead to the overgrowth and aggregation of the material, thus affecting its dispersibility and specific surface area. For the preparation of in-situ carbon-coated transition metal sulfides, the control of the reaction time is particularly important. An appropriate reaction time can ensure that the carbon layer is uniformly coated on the surface of the sulfide crystals, thus improving the stability and electrochemical properties of the material. Too short a reaction time may result in incomplete or defective carbon layer coating, while too long a reaction time may lead to too thick a carbon layer or overgrowth of sulfide crystals.
[0067] The heating rate also has a certain influence on the morphology and properties of the material. A rapid heating rate may cause large thermal stress and expansion rate inside the material, thus affecting its structure and properties. On the contrary, a slow heating rate is beneficial to the heat conduction and uniform temperature distribution inside the material, which is conducive to the slow growth and improvement of crystal structures. In the microwave solvothermal reaction, the control of the heating rate can be achieved by adjusting the microwave power and heating time. An appropriate heating rate can ensure that the reaction system proceeds under mild conditions, which is beneficial to the formation of good morphology and properties of the material.
[0068] Microwave power is one of the key factors affecting the rate and efficiency of microwave solvothermal reactions. A higher microwave power can accelerate the activation of reactants and the crystal growth process, but it may also lead to local overheating of the reaction system and decomposition of the material. Therefore, it is necessary to select an appropriate microwave power to ensure the smooth progress of the reaction and good properties of the material. In the preparation of in-situ carbon-coated transition metal sulfides, the control of microwave power is particularly important. An appropriate microwave power can ensure that the carbon layer uniformly and rapidly coats the surface of the sulfide crystals, thereby improving the electrochemical performance and stability of the material. Excessive microwave power may cause over-sintering of the carbon layer or decomposition of the sulfide crystals, while too low microwave power may make the reaction proceed slowly or incompletely.
[0069] The stirring speed also has a significant impact on the microstructure and properties of the material. An appropriate stirring speed can ensure the uniform mixing and dispersion of reactants in the reaction system, which is beneficial to the uniform growth of crystals and the improvement of the structure. However, too high a stirring speed may lead to an increase in the eddy current on the melt surface and an increase in negative pressure, thereby causing splashing and oxidation of the melt, which has an adverse effect on the properties of the material. In the microwave solvothermal reaction, the control of the stirring speed can be achieved by adjusting the rotation speed and time of the stirrer. An appropriate stirring speed can ensure the full mixing and reaction of reactants in the reaction system, which is beneficial to the formation of good morphology and properties of the material.
[0070] In this invention, transition metal sulfides are synthesized using MOF materials as precursors, retaining the carbon framework of the precursor MOF, saving the steps required for additional carbon coating. Moreover, this invention synthesizes in-situ carbon-coated transition metal sulfides by microwave solvothermal method, greatly shortening the synthesis time and optimizing the preparation process of in-situ carbon-coated transition metal sulfides.
[0071] This invention does not limit the source of the MOF material, which can be directly obtained by purchase or synthesized according to existing technologies. For example, the MOF material is purchased from Shanghai Kaishu Chemical Technology Co., Ltd., with CAS numbers 222404-02-6 or 1189182-67-9.
[0072] When the MOF material is synthesized according to existing technologies, the preparation steps of the MOF material are as follows: Dissolve the metal coordination ion compound and the organic compound in a mixed solvent of deionized water and absolute ethanol, and obtain the MOF material through microwave solvothermal reaction.
[0073] In the preparation examples of the MOF material, the volume ratio of deionized water to absolute ethanol is (1 - 3):1. Exemplarily, the volume ratio of deionized water to absolute ethanol is 3:1, 1:1, or 2:1.
[0074] In the preparation examples of MOF materials, the metal coordination ion compound includes one of Fe(NO3)3·9H2O, Cu(NO3)2·3H2O, Co(NO3)2·6H2O, (NH4)6Mo7O 24 ·4H2O and Ni(NO3)2·6H2O.
[0075] In the preparation examples of MOF materials, the organic compound includes one of trimesic acid (1,3,5-benzenetricarboxylic acid), trimellitic acid (1,2,4-benzenetricarboxylic acid), pyromellitic acid (1,2,3-benzenetricarboxylic acid) and pyromellitic acid hydrate.
[0076] In the preparation examples of MOF materials, the mass ratio of the metal coordination ion compound to the organic compound is (1-5):(1-10). Exemplarily, the mass ratio of the metal coordination ion compound to the organic compound is 2:1, 1:1, 4:1, 1:6, 1:10, 1:5, 3:1, 5:1, 5:7, 1:4, 1:2 or 2:5.
[0077] In the preparation examples of MOF materials, the parameters of the microwave solvothermal reaction are: the reaction temperature is 80-200 °C, the reaction time is 30-120 min, the heating rate is 5-10 °C / min, the microwave power is 300-800 W, and the stirring speed is 800-2000 rpm.
[0078] Compared with directly purchasing MOF materials, the cost of preparing MOF materials using metal coordination ion compounds and organic compounds is lower.
[0079] The in-situ carbon-coated transition metal sulfide provided by the embodiments of the present invention can be used to prepare battery energy storage materials. For example, it can be used to prepare the negative electrode materials for battery energy storage, such as the negative electrode materials for sodium ion batteries.
[0080] The principle of the present invention is as follows: The present invention uses a metal-organic framework MOF material as a precursor and adopts microwave hydrothermal method to directly prepare in-situ carbon-coated transition metal sulfide in one step. The method of the present invention utilizes the direct action of microwave radiation on polar molecules to generate heat energy through molecular friction, realizing bulk heating. The energy transfer is more direct, greatly shortening the reaction time; and the reaction controllability is better, and the product uniformity is better.
[0081] In the embodiments and comparative examples of the present invention, except for MOF materials, other raw materials and reagents are purchased. Exemplarily, when assembling the battery, the conductive agent used is conductive carbon black (SP), purchased from Duoduo Chemical Reagent Network, model SuperP Li; carboxymethyl cellulose is purchased from Duoduo Chemical Reagent Network, model CMC2200; the binder is styrene-butadiene rubber binder (SBR), purchased from Duoduo Chemical Reagent Network, model SBRBM-451B; the solvent of the electrolyte in the battery is an electrolyte solvent system composed of ethylene glycol dimethyl ether (DME); the glass fiber separator is GF / D glass fiber separator, purchased from Guangzhou Boao Inda Instrument Co., Ltd.; copper sulfide is purchased from Shanghai Aladdin Biotechnology Co., Ltd.
[0082] Unless otherwise specified, the room temperature in the present invention is 25±2°C.
[0083] It should be pointed out that the matters not described in detail in the present invention are conventional operating means in the art and are not the focus of the present invention.
[0084] The technical solution of the present invention is further illustrated by the following embodiments.
[0085] Example 1
[0086] Preparation of MOF materials:
[0087] (1) First, weigh 1 g of Cu(NO3)2·3H2O and then weigh benzene trimeric acid (the mass ratio of Cu(NO3)2·3H2O to benzene trimeric acid is 1:2), and fully dissolve and mix them in a mixed solution of 80 mL of deionized water and 80 mL of anhydrous ethanol. Then, transfer the dissolved solution to the lining of a microwave hydrothermal synthesizer, raise the temperature to 100°C at 10°C / min under a microwave power of 700 W and react for 60 min. The stirring speed is 800 rpm to obtain a MOF material.
[0088] (2) The MOF material and thioacetamide obtained in step (1) are weighed in a mass ratio of 1:4, and then the weighed materials are placed in a mixed solution of 120 mL of deionized water and 40 mL of anhydrous ethanol for thorough dissolution and mixing, and then the dissolved solution is transferred to the lining of a microwave hydrothermal synthesizer, and the temperature is raised to 200 ° C at 10 ° C / min at a microwave power of 700 W for 1 hour, and the stirring speed is 2000 rpm to obtain in situ carbon-coated transition metal copper sulfide.
[0089] The morphology of the in-situ carbon-coated transition metal copper sulfide in this embodiment is shown in FIG. Figure 1 As shown, the prepared in situ carbon-coated transition metal sulfide has a two-dimensional layered structure, which can accelerate the migration of sodium ions and speed up the electrochemical reaction kinetics.
[0090] Effect verification 1
[0091] (1) Battery assembly:
[0092] Weigh the in-situ carbon-coated transition metal copper sulfide material, conductive carbon black (SP), carboxymethyl cellulose (CMC), and binder (SBR) in Example 1 according to a mass ratio of 80:10:5:5. Then mix and grind the in-situ carbon-coated transition metal copper sulfide, conductive carbon black, and carboxymethyl cellulose for 30 minutes and put them into a mixer. After adding 1 g of distilled water for every 2 g of the above materials, rotate at a speed of 2000 rpm for 30 minutes. Finally, add the binder and rotate at a speed of 200 rpm for 5 minutes to form a black-gray slurry. Coat the slurry on the copper foil current collector with a thickness of 100 μm and dry it in a vacuum at 60 °C for 12 h to obtain the in-situ carbon-coated copper sulfide electrode sheet. Use the in-situ carbon-coated copper sulfide electrode sheet as the negative electrode material of the sodium-ion battery and assemble the battery in a glove box filled with argon. The assembly process is as follows: Cut the dried electrode sheet into circular electrode sheets with a diameter of 13 mm using a punching machine. Use 1.0 M NaPF6 in DME = 100 Vol% as the electrolyte, a GF / D glass fiber membrane as the separator, a sodium sheet with a diameter of 15 mm as the reference electrode and counter electrode, and a CR2016 type stainless steel as the battery case to assemble a button-type sodium-ion negative electrode battery.
[0093] Replace the in-situ carbon-coated copper sulfide electrode sheet in Example 1 with commercial copper sulfide (i.e., use commercial copper sulfide as the negative electrode material of the button-type sodium-ion negative electrode battery), and assemble a button-type sodium-ion negative electrode battery in the same way for performance comparison with the battery assembled from the product of Example 1.
[0094] (2) Test the electrochemical performance:
[0095] After standing the two prepared batteries at 25 °C for 8 h, first cycle them at a rate of 0.05 A·g -1 for 3 cycles; then perform charge-discharge cycle tests at rates of 1 A·g -1 and 5 A·g -1 between 0.01 V and 3.0 V. The cycle performance curve and Coulomb efficiency curve of the battery assembled from the product of Example 1 at a current density of 1 A·g -1 are as shown in Figure 2 . The cycle performance curve and Coulomb efficiency curve of the battery assembled in Example 1 at a current density of 5 A·g -1 are as shown in Figure 3 . The cycle performance curve and Coulomb efficiency curve of the battery assembled in Example 1 at a low temperature of -20 °C and a current density of 0.1 A·g -1 are as shown in Figure 4 .
[0096] The test results show that the initial discharge specific capacity of the button-type sodium-ion negative electrode battery assembled with commercial copper sulfide is 253.3 mAh / g, the Coulomb efficiency of the first cycle is 53.75%, and it can only cycle 800 times, as shown in -1 shown. The battery assembled in Example 1 has an initial discharge specific capacity of up to 458.5 mAh / g at a current density of 1 A·g Figure 5 -1 , the Coulomb efficiency of the first cycle is as high as 94.3%, and the specific capacity remains at 378.5 mAh / g and the Coulomb efficiency remains at 100% after 1000 cycles; and there is still a capacity of 351.2 mAh / g after cycling 1000 times at a high current density of 5 A·g -1 . The battery assembled in Example 1 has an initial discharge specific capacity of up to 527.1 mAh / g at a low temperature of -20 °C and a current density of 0.1 A·g -1 , the Coulomb efficiency of the first cycle reaches 86.88%, and the specific capacity remains at 370.7 mAh / g and the Coulomb efficiency remains at 100% after 140 cycles. The above data prove that the battery prepared by using the in-situ carbon-coated transition metal sulfide of the present invention has excellent performance in terms of low temperature, high capacity and fast charging.
[0097] As can be seen from the above, the sodium-ion battery prepared with the in-situ carbon-coated transition metal copper sulfide in Example 1 as the negative electrode material has excellent cycle performance and fast charging characteristics. It can be seen that the in-situ carbon-coated copper sulfide material prepared by the novel microwave synthesis method of the present invention not only improves the capacity and cycle characteristics of the battery, but also improves its fast charging performance.
[0098] Example 2
[0099] (1) Preparation of in-situ carbon-coated copper sulfide material:
[0100] First, weigh 1 g of Cu(NO3)2·3H2O, and then weigh benzene tricarboxylic acid (the mass ratio of Cu(NO3)2·3H2O to benzene tricarboxylic acid is 1:3), and fully dissolve and mix it in a mixed solution of 90 mL of deionized water and 30 mL of absolute ethanol. Then transfer the dissolved solution to the inner lining of a microwave hydrothermal synthesizer, heat it to 80 °C at a rate of 5 °C / min under a microwave power of 300 W and react for 120 min, with a stirring speed of 1000 rpm to obtain a MOF material;
[0101] (2) Weigh the MOF material obtained in step (1) and thiourea according to a mass ratio of 1:10. Then, put the weighed materials into a mixed solution of 80 mL of deionized water and 80 mL of absolute ethanol for full dissolution and mixing. Then, transfer the dissolved solution to the inner lining of a microwave hydrothermal synthesizer and react at 200 °C at a microwave power of 800 W for 60 min at a stirring speed of 1500 rpm to obtain copper sulfide coated with in-situ carbon.
[0102] Assemble a button-type sodium-ion negative electrode battery by the assembly method in (1) of Effect Verification 1, and then conduct an electrochemical performance test in the manner of (2) in Effect Verification 1. At a current density of 1 A·g -1 The initial discharge specific capacity is 432.6 mAh / g, the first-cycle Coulombic efficiency is 92.5%, and the specific capacity remains at 414.1 mAh / g and the Coulombic efficiency remains at 99.74% after 1000 cycles; and at a large current density of 5 A·g -1 There is still a capacity of 311.2 mAh / g after 1000 cycles.
[0103] Example 3
[0104] (1) Preparation of in-situ carbon-coated copper sulfide material:
[0105] First, weigh 1 g of Cu(NO3)2·3H2O, and then weigh benzene-1,3,5-tricarboxylic acid (the mass ratio of Cu(NO3)2·3H2O to benzene-1,3,5-tricarboxylic acid is 1:2). Conduct full dissolution and mixing in a mixed solution of 60 mL of deionized water and 60 mL of absolute ethanol. Then, transfer the dissolved solution to the inner lining of a microwave hydrothermal synthesizer and heat it to 100 °C at a rate of 5 °C / min at a microwave power of 300 W and react for 100 min at a stirring speed of 1000 rpm to obtain the MOF material;
[0106] (2) Weigh the MOF material obtained in step (1) and sodium thiosulfate according to a mass ratio of 4:1. Then, put the weighed materials into a mixed solution of 80 mL of deionized water and 80 mL of absolute ethanol for full dissolution and mixing. Then, transfer the dissolved solution to the inner lining of a microwave hydrothermal synthesizer and heat it to 200 °C at a rate of 10 °C / min at a microwave power of 800 W and react for 120 min at a stirring speed of 1000 rpm to obtain copper sulfide coated with in-situ carbon.
[0107] Assemble a button-type sodium-ion negative electrode battery by the assembly method in (1) of Effect Verification 1, and then conduct an electrochemical performance test in the manner of (2) in Effect Verification 1. At a current density of 1 A·g -1At the current density of 5A·g, the first discharge capacity is 421.9mAh / g, the first cycle coulomb efficiency is 93.8%, and after 1000 cycles, the capacity remains at 389.7mAh / g and the coulomb efficiency remains at 99.6%. -1 After 1000 cycles at high current density, the capacity is still 304.5mAh / g.
[0108] Example 4
[0109] (1) Preparation of in-situ carbon-coated copper sulfide materials:
[0110] First, 1 g of Cu(NO3)2·3H2O and benzenetricarboxylic acid (the mass ratio of Cu(NO3)2·3H2O to benzenetricarboxylic acid is 1:1) are weighed, and the mixture is fully dissolved and mixed in a mixed solution of 60 mL of deionized water and 60 mL of anhydrous ethanol. The dissolved solution is then transferred to the inner lining of a microwave hydrothermal synthesizer, and the temperature is raised to 80°C at 5°C / min under a microwave power of 300 W and reacted for 60 min. The stirring speed is 1500 rpm to obtain a MOF material.
[0111] (2) The MOF material obtained in step (1) and sodium thiosulfate are weighed in a mass ratio of 4:10, and then the weighed materials are placed in a mixed solution of 80 mL of deionized water and 80 mL of anhydrous ethanol for thorough dissolution and mixing, and then the dissolved solution is transferred to the lining of a microwave hydrothermal synthesizer, and the temperature is raised to 200 ° C. at a microwave power of 800 W at a rate of 10 ° C. / min for reaction for 120 min, and the stirring speed is 2000 rpm to obtain in situ carbon-coated metal copper sulfide.
[0112] The button-type sodium ion negative electrode battery was assembled by the assembly method of effect verification 1 (1), and then the electrochemical performance test was carried out by the method of effect verification 1 (2). -1 At the current density of 5A·g, the first discharge capacity is 429.7mAh / g, the first cycle coulomb efficiency is 93.2%, and after 1000 cycles, the capacity remains at 401.2mAh / g and the coulomb efficiency remains at 99.7%. -1 After 1000 cycles at high current density, the capacity is still 327.5mAh / g.
[0113] Example 5
[0114] (1) Preparation of in-situ carbon-coated copper sulfide materials:
[0115] First, weigh 1 g of Cu(NO3)2·3H2O, and then weigh benzene - tricarboxylic acid (the mass ratio of Cu(NO3)2·3H2O to benzene - tricarboxylic acid is 1:3). Dissolve and mix them thoroughly in a mixed solution of 90 mL of deionized water and 30 mL of absolute ethanol. Then transfer the dissolved solution to the inner liner of a microwave hydrothermal synthesizer. Under a microwave power of 300 W, heat it to 80 °C at a rate of 5 °C / min and react for 120 min with a stirring speed of 2000 rpm to obtain the MOF material;
[0116] (2) Weigh the MOF material obtained in step (1) and thioacetamide according to a mass ratio of 1:6. Then put the weighed materials into a mixed solution of 80 mL of deionized water and 80 mL of absolute ethanol for thorough dissolution and mixing. Then transfer the dissolved solution to the inner liner of a microwave hydrothermal synthesizer. Under a microwave power of 800 W, heat it to 200 °C at a rate of 10 °C / min and react for 60 min with a stirring speed of 1500 rpm to obtain in - situ carbon - coated copper sulfide.
[0117] Assemble a button - type sodium - ion negative electrode battery by the assembly method in (1) of Effect Verification 1, and then conduct electrochemical performance testing in the manner of (2) in Effect Verification 1. At a current density of 1 A·g -1 The initial discharge specific capacity is 425.7 mAh / g, the initial coulombic efficiency is 92.8%, and after 1000 cycles, the specific capacity remains at 392.5 mAh / g and the coulombic efficiency remains at 99.8%; and at a large current density of 5 A·g -1 After 1000 cycles, there is still a capacity of 311.4 mAh / g.
[0118] Effect Verification 2
[0119] By only modifying the relevant reaction conditions in Example 5, prepare different types of in - situ carbon - coated transition metal sulfides, and then assemble a button - type sodium - ion negative electrode battery by the assembly method in (1) of Effect Verification 1, and then conduct electrochemical performance testing in the manner of (2) in Effect Verification 1. The test results at a current density of 0.1 A·g -1 are shown in Table 1.
[0120] Table 1
[0121]
[0122]
[0123] Note: In Table 1, the first column "Reaction temperature (℃) and time (min)" from left to right indicates the reaction temperature and time for preparing MOF materials; the second column "Reaction temperature (℃) and time (min)" indicates the reaction temperature and time for preparing in situ carbon-coated transition metal sulfides; wherein, the former indicates the reaction temperature, and the latter indicates the reaction time, for example, "180 / 30" means reacting at 180℃ for 30min.
[0124] Comparative Example 1
[0125] The raw materials were weighed according to the mass ratio of Cu(NO3)2·3H2O and thiourea of 2:1, and fully dissolved and mixed in a mixed solution of 90 mL of deionized water and 30 mL of anhydrous ethanol. The dissolved solution was then transferred to a high-pressure reactor, heated to 180°C at 5°C / min and reacted for 12 hours to obtain copper sulfide. The morphology is shown in the figure. Figure 6 As shown, its morphology is that of particles with uneven sizes. Its uneven size does not accelerate the electrochemical reaction process of sodium ions, so its electrochemical performance is poor.
[0126] Comparative Example 2
[0127] Traditional method for preparing copper sulfide in one step:
[0128] Copper powder and sulfur powder were mixed in a mass ratio of 2:1, heated to 450°C at 5°C / min in an argon atmosphere, and heated for 6 hours to obtain copper sulfide.
[0129] Effect verification 3
[0130] The product of comparative example 1-2 was assembled into a button-type sodium ion negative electrode battery according to the assembly method of effect verification 1 (1), and then the electrochemical performance test was carried out in the manner of effect verification 1 (2).
[0131] The cycle performance curve and Coulomb efficiency curve of the battery assembled with the product of Comparative Example 1 are as follows: Figure 7 The test results show that the first discharge capacity of the battery assembled with copper sulfide in comparative example 1 is only 161.7 mAh / g, and the first cycle coulomb efficiency is only 54.28%. -1 The battery assembled with the product prepared by the preparation method of Comparative Example 1 has a low specific capacity and a short cycle life. The product prepared by the preparation method of Comparative Example 1 is not suitable for direct application in the negative electrode of a sodium ion battery.
[0132] The first discharge capacity of the battery assembled with copper sulfide in Comparative Example 2 is only 205.7 mAh / g. -1 It can only cycle up to 300 times.
[0133] The above are only the preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention. Therefore, the protection scope of the present invention should be subject to the protection scope of the claims.
Claims
1. A method for preparing in-situ carbon-coated transition metal sulfide, characterized in that, Including the following steps: Adding a metal-organic framework material and a sulfur source into a mixed solvent, and obtaining in-situ carbon-coated transition metal sulfide through microwave solvothermal reaction.
2. The method for preparing the in-situ carbon-coated transition metal sulfide according to claim 1, wherein, The mass of the sulfur source is 0.25 - 10 times the mass of the metal-organic framework material.
3. The method for preparing in-situ carbon-coated transition metal sulfide according to claim 2, wherein The sulfur source includes one of thiourea, sodium thiosulfate, and thioacetamide.
4. The method for preparing in-situ carbon-coated transition metal sulfide according to claim 1, wherein The mixed solvent is a mixed solvent of deionized water and absolute ethanol.
5. The method for preparing in-situ carbon-coated transition metal sulfide according to claim 1, wherein The microwave solvothermal reaction is carried out under stirring conditions.
6. The method for preparing in-situ carbon-coated transition metal sulfide according to claim 5, wherein The parameters of the microwave solvothermal reaction are: reaction temperature is 80 - 200 °C, reaction time is 30 - 120 min, heating rate is 5 - 10 °C / min, microwave power is 300 - 800 W, and stirring speed is 800 - 2000 rpm.
7. An in-situ carbon-coated transition metal sulfide, characterized in that, Prepared according to any one of claims 1 - 6.
8. Use of the in-situ carbon-coated transition metal sulfide according to claim 7 in the preparation of battery energy storage materials.
9. The application according to claim 8, wherein The battery energy storage material is a battery energy storage negative electrode material.
10. The application according to claim 9, wherein The battery energy storage negative electrode material is a sodium-ion battery negative electrode material.